Comparison of Community-Acquired Pneumonia Requiring Admission to Hospital in HIV-and Non-HIV-Infected Patients - Claire Touchie; Thomas J Marrie (Canadian Journal of Infectious Diseases)
OBJECTIVE: To compare community-acquired pneumonia (CAP) in hospitalized human immunodeficiency virus (HIV)-infected patients with that in hospitalized non-HIV-infected patients by assessing presenting characteristics, etiology and outcomes.